Analysis of Organizational Commitment, Compensation and Job Satisfaction on Official Performance at the Nganjuk Regency Cooperatives and Micro Enterprises Office - Dariyanti, Suci; Leksono, Poniran Yudho (Universitas Nusantara PGRI Kediri, 2025)
Research-aim : The-purpose of-this study isto test whether Organizational Commitment, Compensation and Job-Satisfation-on Official-Peformance at-the Nganjuk Regency Coperatives-and Micro-Enterpries Office Design/Methode/Approach: The method-i this-study is-quantitative-based. -Samples were taken using the samplin technique The sampling techniqe used by the researcher was saturated sampling technique and a sampleof 44 respondents was obtained from the results of filling out a questionnaire to Officials of the Nganjuk Regency-Cooperatives and Micro-Enterprises-Office Analysis and data processing using SPSS 25 software Research Finding : The variables of Organizational-Commitment, Compensation andJob Satisfactionpartially and-simultaneously have a significant-effect on-Official performancs at the Nganjuk Regency-Cooperatives and Micro-Enterprises-Office Theoretical contribution/Originality : The researcher hopes that the resuls of-this study can Nganjuk Regency-Cooperatives and Micro-Enterprises-Office develop knowledge Nganjuk Regency-Cooperatives and Micro-Enterprises-Office and the basis of thinking to help make a solution to overcome the phenomenon that occurs in this research. In addition, it can also be a study material for future research development, especially in the field of coaching and Official performance development Practitionel/Policy implication : The hope-is for future researchers to furthe develop fromthe limitation of-this study, such as data-obtained is only-sourced fromquestionnaires and limited-sampleis and more relevant examiner variables. Research limitation : The limitations of-this study-are that the variables used are less than optimal to represent and the research object is limited to Officials of the Nganjuk Regency Cooperatives and Micro Enterprises Office